Subsurface Water Retention a Technology for Increasing the Field Use Efficiency and Water Saving Values of Cucumber Plant (Journal of Engineering, 2019)
The technology of subsurface soil water retention (SWRT) uses a polyethylene ‎trough that is fixed under the root zone of the plant. It is a modern technology to increase the values of water ‎use efficiency, plant productivity and saving irrigation water by applying as little irrigation water ‎as possible. This study work aims at improving the crop yield and water use efficiency of a cucumber plant with less applied irrigation water by installing membrane trough below the soil surface. The field experiment was conducted in the Hawr Rajab District of ‎Baghdad Governorate in Winter 2018 for testing various trickle irrigation ‎systems. Two agricultural ‎treatment plots were utilized in a greenhouse for the comparison. Plot T1 has used ‎a subsurface trickle irrigation together with membrane trough.  Plot T2 has used only ‎surface trickle irrigation system without using SWRT. The total area of the plots T1and T2 was 13.2 ‎m2 and 6.66 m2, respectively. The obtained results of the study confirmed that the plot T1 satisfies values greater than plot ‎T2 in terms of crop yield, field water use efficiency and in saving the applied irrigation water. The increase rate of field water use efficiency and crop yield in plot T1 compared with plot T2 was 103 %, ‎and 24 %, respectively. Additionally, the increase rate in saving the applied irrigation water ‎in plot T1 comparing with plot T2 was 64 %. The installation of the membrane trough below the plant’s root zone together with subsurface trickle irrigation system assisted in keeping the water, nutrients, and fertilizers during the root zone profile, improving the field water use efficiency and then the parameter of water productivity.‎  Subsurface trickle irrigation, subsurface water retention technology, yield, ‎water use efficiency.